Syntactic and Semantic Analysis of Clauses Introduced by Slovenian Koli-Pronouns - Gregorčič, Kristina; Gabrovšek, Dejan (Slavia Centralis, 2024)
The aim of this paper is to illustrate the syntactic environments and the semantic features of clauses introduced by Slovenian koli-pronouns (also known as randomness relative pronouns), and to place them in the broader context of cross-linguistic research. Koli-pronouns express arbitrariness and freedom of choice, and thus introduce clauses that name sets of equally selectable referents or conditions. Depending on the type of complementation required by the superordinate clause, koli-pronouns can introduce nominal or adverbial clauses, functioning as subjects, objects, subject complements, object complements or adverbial adjuncts. They can also introduce disjuncts, which express the speaker’s attitude to the utterance, or conjuncts, which serve to link clauses or larger units of text.